Considerations on the Internationalization of Ukrainian Enterprises in the Context of their Innovation - Chebotarov, Viacheslav; Chebotarov, Iegor (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
The level of internationalization and innovation of Ukrainian enterprises is relatively low - as is the level of innovation in the Ukrainian economy. There is no relevant internationalization and innovation policy in this country. There are also no systemic changes in the field of support for entrepreneurs and protection of intellectual property, therefore in the near future it is rather impossible to achieve a sustainable competitive advantage based on innovations. There is a need for a coherent and transparent state policy to support both processes: internationalization of enterprises and their innovations.